New and less known Orthoptera (Insecta) from the island of Socotra (Yemen) - Massa, Bruno (Zootaxa, 2009)
A list of nine species of Orthoptera collected on Socotra is reported. Three of them were previously unrecorded on the island (Trigonidium cicindeloides, Paratettix subpustulatus and Acrotylus insubricus) and one (Ochrilidia socotrae n.sp.) was undescribed. Further systematic notes on Glomeremus pileatus, G. mediopictus, Pyrgomorpha conica tereticornis, Acrotylus incarnatus and Sphingonotus insularis are included. The East African Acrotylus meruensis, previously considered synonym of A. incarnatus, is proposed as a valid species, distinct from the latter.